EVALUASI KUALITAS AIR MINUM DAN SANITASI LINGKUNGAN LAPAS KELAS II B BANGKINANG DAN PASIR PANGARAIAN PROVINSI RIAU - Zurrahmi Z. R; Mirna Ilza; Dedi Afandi (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2019)
This study aims to evaluate the drinking water quality and environment sanitation in Class II B Prison Bangkinang and Pasir Pangaraian, Riau Province. The study was conducted for 2 (two) months. Survey method is employed in this study. To evaluate the quality of drinking water based on physical, chemical, and bacteriological parameters, the observation sheet based on Permenkes No.492 / Menkes / Per / IV / 2010 is employed, while observation checklist adopted from guidelines for handling prison in prison and remand center, Ministry of Justice and Human Rights, is employed to evaluate the environment sanitation. The findings showed that the drinking water quality of Class II B Bangkinang and Pasir Pengaraian based on physical, chemical and bacteriological parameters meet the requirements due to does not exceed the standard quality. Whereas, the environment sanitation is in the good category generally because the score on the observation sheet exceeds the minimum score of8. It could be stated that the quality of drinking water in Class II B Prisons Bangkinang is better than Class II B Prisons Pasir Pangaraian. Dealing with the findings of the study it is suggested to have regular and periodic check to examine the drinking water quality, water hygiene, and food quality to ensure the prisoner health. In further, the future researchers are suggested to have a flexible and depth acces to achieve better information and accurate method.